Manajemen Pembiayaan Pendidikandi Madrasah Aliyah Darussalam Sumedang - Ari Prayoga; Arif Risnandi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2019)
Funding management at Madrasah Aliyah Darussalam Sumedang has obstacles in reporting administratively monthly financing. There are some cases of students whose financial report books have not been recorded in the books big treasurer. This study aims to reveal the management financing includes; planning, analysis, strategy and evaluation of financing education at Madrasah Aliyah Darussalam Sumedang. Research methods that used is qualitative. Collection techniques using interview techniques structured, participatory observation techniques and documentation techniques. Research result shows that; First, the financing planning process is carried out by compiling data formats for submitting budget submissions from the madrasah education section of Sumedang district. Second, the financing analysis is carried out by the head of the madrasah and vice principal of the madrasah in meeting the needs of the institution, this discussed at the meeting. Third, system development and management accountable costs, madrasas carry out the procedure for procurement of goods and services within the scope of madrasa needs from facilities and infrastructure, management operations carried out by the treasurer in managing expenses and financial income from students. Fourth, the evaluation is carried out by the madrasah involved the madrasah community, the madrasah treasurer as the executor as well as the head of the madrasah as the policy decision maker cost management.